Increases in Intimate Partner Violence During COVID-19: Prevalence and Correlates - Peitzmeier, Sarah M.; Fedina, Lisa; Ashwell, Louise; Herrenkohl, Todd I.; Tolman, Rich (Journal of interpersonal violence, 2022)
Measures to contain the global COVID-19 pandemic led to stay-at-home orders across the world, accompanied by fears of a global surge in intimate partner violence (IPV). We administered an online general-population survey to 1169 women and transgender/nonbinary individuals throughout the state of Michigan in June–August 2020 to assess changes in the prevalence, severity, and correlates of IPV during the COVID-19 pandemic. Quota sampling was used to match the racial/ethnic and urban/rural distribution of the state. More than one in seven (15.1%) participants reported physical, sexual, psychological, or technology-facilitated IPV since COVID, similar to the prevalence in the 3 months before COVID (16.2%). However, there were indications that IPV severity increased and that novel cases of IPV are occurring in relationships that previously had no abuse. A majority (64.2%) of individuals who experienced IPV since COVID reported that the IPV was new to the relationship (34.1%) or of increased severity during COVID-19 (26.6%), representing 9.7% of the overall sample. New or increased IPV was significantly more prevalent among those who were essential workers, pregnant, unable to afford rent, unemployed/underemployed or had recent changes to their job, had partners with recent changes to employment, and those who had gotten tested or tested positive for COVID-19. Urban residence, trans/nonbinary identity, and having a toddler were more strongly associated with IPV during COVID as compared to before COVID. While findings do not support significant changes in the overall prevalence of IPV, the majority of survivors reported incident IPV in relationships that had not previously been abusive, or IPV that became more severe since the start of the pandemic. Cases of new or increased IPV were more concentrated in marginalized groups. Potential touchpoints for outreach and services during future lockdowns include prenatal and pediatric settings, daycares, employers of essential workers, and COVID-19 testing centers. Policies providing rental, childcare, and unemployment support may mitigate increases in IPV during COVID-19.